Characteristics of Pozzolan and Composite Portland Cements for Sustainable Concrete's Material - Ni Nyoman Kencanawati; Shofia Rawiana; Ni Putu Ria Ria Darmayanti (Graduate Program of Syiah Kuala University, 2020)
To support sustainable materials, the ordinary Portland cement production has been reduced since it left a high carbon footprint during manufacturing. As an alternative, the use of pozzolan Portland cement and composite Portland cement has been encouraged because they are more environmentally friendly. This paper examines some characteristics of cement made from pozzolan Portland cement (P.P.C.) and composite Portland cement (P.C.C.). The testing procedures were carried out on chemical and physical testing on P.P.C. and P.C.C. In addition, the mechanical testing of concrete made from both types of Portland cement and their combinations were conducted under compression load. Furthermore, the surface hardness of the concrete was evaluated using a rebound hammer measurement. Concrete testing was conducted after the curing age of 7, 28, and 42 days. According to chemical examination, P.P.C. has higher silica (SiO2) and iron (Fe2O3) than those of P.C.C., whereas P.C.C. has a higher lime (CaO) content. Compared to P.P.C., P.C.C. shows faster initial and final setting time. This result is proportionally influencing the strength development of concrete. P.C.C. concrete offers significant strength development at an earlier age. Meanwhile, P.P.C. concrete reacts slower at an earlier age, but it improves the compressive strength at a later age. The mix combination of 50% P.P.C. and 50% P.C.C. in concrete shows the highest average compressive strength and surface hardness. This combination achieves the average compressive strength of 30.27 MPa, 35.27 MPa, and 35.93 MPa respectively for 7, 28, and 42 days curing time. Furthermore, this concrete also shows the most remarkable characteristics of Young's modulus and surface hardness